Diabetes, hypertension, overweight and hyperlipidemia and 7-day case-fatality in first myocardial infarction. (September 2016) - Quintana, H.K.; Janszky, I.; Gigante, B.; Druid, H.; Ahlbom, A.; Hallqvist, J.; de Faire, U.; Leander, K.
Abstract: Background: Out-of-hospital deaths due to a first myocardial infarction (MI) are frequent and a big challenge for prevention. Increased knowledge about factors influencing MI fatality is needed. Metabolic risk factors have been studied in relation to MI fatality in-hospital but studies considering also out-of-hospital deaths are few. Aim: To assess how diabetes and other metabolic risk factors associate with death within 7 days after first time MI among subjects aged between 45 and 70 identified in Stockholm County 1992–1994. Methods: Data were collected using questionnaires (close relatives of fatal cases were asked to fill the questionnaire), physical examinations, national registers and autopsy reports. Risk ratios (RR) of 7-day MI fatality with 95% confidence intervals (CI) associated with the risk factors under study were calculated using binomial regression with log link. Results: Out of 1905 first time MI cases included, 524 died within 7 days. After adjustments for age, sex, current smoking, education and general comorbidity, diabetes, but not hypertension and hyperlipidemia, was associated with MI fatality (RR 1.68, 95% CI 1.20–2.28). Overweight, as compared to normal BMI, was inversely associated with MI fatality (multiple adjusted RR 0.68, 95% CI 0.49–0.94); obesity results pointed in the same direction (multiple adjusted RR 0.79, 0.52–1.16). Conclusions: In this population-based inception cohort study, diabetes but not hypertension and hyperlipidemia were associated with MI fatality. This further emphasizes the importance of diabetes as a cardiovascular risk factor and the need for close surveillance of diabetic patients. Overweight was however associated with decreased MI fatality.